Skyhunter - Lu, Marie, 1984- (Roaring Brook Press, 2020)
The Karensa Federation has conquered a dozen countries, leaving Mara as one of the last free nations in the world. Refugees flee to its borders to escape a fate worse than death, transformation into mutant war beasts known as Ghosts, creatures the Federation then sends to attack Mara. The legendary Strikers, Mara's elite fighting force, are trained to stop these monsters. But as the number of Ghosts grows and Karensa closes in, defeat seems inevitable. Still, one Striker refuses to give up hope. Robbed of her voice and home, Talin Kanami knows firsthand the brutality of the Federation. After another devastating battle, Mara seems ready to fall. But when a mysterious prisoner is brought from the front, Talin senses there's more to him than meets the eye. Is he a spy from the Federation? Or could he be the weapon that will save them all?